Remembering ICC 16 - Hohn, Keith L. (My University, 2016)
Every four years, a group of outstanding individuals, the best in their field, come together from all over the world. These individuals have spent years learning their craft, and now they assemble to show what they can do. Such a gathering happened in 2016.
Citation: Hohn, K. (2016). Remembering ICC 16. Catalysts, 6(10), 1. doi:10.3390/catal6100153
Keywords: Chemistry